Positive electrode slurry for lithium-sulfur battery, positive electrode for lithium-sulfur battery manufactured using the same, and lithium-sulfur battery containing the same

By adjusting the ratio and phase angle of the average particle size of the positive electrode active material and the positive electrode slurry, the problem of insufficient dispersion and fluidity of the lithium-sulfur battery positive electrode slurry under high solids content is solved, and battery performance improvement and manufacturing process optimization are achieved.

CN114982005BActive Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180008751.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-09
Filing Date
2021-09-10
Publication Date
2025-02-28
Estimated Expiration
2041-09-10

AI Technical Summary

Technical Problem

The existing lithium-sulfur battery positive electrode slurry is insufficient in dispersion and fluidity under high solid content, resulting in deterioration of battery performance and low manufacturing process efficiency.

Method used

By adjusting the ratio of the average particle size of the positive electrode active material and the positive electrode slurry, it is ensured to be less than 1.5, and the phase angle at 1 Hz is maintained above 50°, thereby improving the flowability and processability of the positive electrode slurry.

Benefits of technology

The excellent fluidity and cohesion of the cathode slurry under high solid content conditions are achieved, and the electrochemical performance of the cathode of the lithium-sulfur battery is improved, and the productivity and economic feasibility of the manufacturing process of the lithium-sulfur battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003739335380000201
    Figure BDA0003739335380000201
Patent Text Reader

Abstract

The present invention relates to a positive electrode slurry for a lithium-sulfur battery, a positive electrode for a lithium-sulfur battery manufactured using the positive electrode slurry, and a lithium-sulfur battery containing the positive electrode slurry, and more specifically, to a positive electrode slurry for a lithium-sulfur battery, the positive electrode slurry comprising a positive electrode active material, a conductive material, a binder and a solvent, wherein the average particle size (D 50 ) and the average particle size (D 50 ) is less than 1.5, and the phase angle of the positive electrode slurry at 1 Hz is greater than 50°. The positive electrode slurry for lithium-sulfur batteries of the present invention exhibits excellent fluidity even when the solid content is high, thereby making it possible to manufacture a positive electrode for lithium-sulfur batteries with excellent electrochemical properties, and to improve the productivity and economic feasibility of the manufacturing process of the positive electrode for lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0121526 filed on September 21, 2020 and Korean Patent Application No. 10-2021-0120228 filed on September 9, 2021, the entire contents of which are incorporated herein by reference.

[0002] The invention relates to a positive electrode slurry for a lithium-sulfur battery, a preparation method thereof, a positive electrode for a lithium-sulfur battery comprising the positive electrode slurry, and a lithium-sulfur battery. Background Art

[0003] As the use range of lithium secondary batteries expands not only to portable electronic devices and communication devices but also to electric vehicles (EVs) and electric power storage systems (ESSs), demand for high capacity of lithium secondary batteries used as their power sources has been growing.

[0004] Among various lithium secondary batteries, lithium-sulfur batteries are battery systems that use a sulfur-based material having a sulfur-sulfur bond as a positive electrode active material and lithium metal, a carbon-based material in which lithium ions are intercalated / deintercalated, or silicon or tin that forms an alloy with lithium as a negative electrode active material.

[0005] The advantages are that sulfur, which is the main material of the positive electrode active material in the lithium-sulfur battery, has a low atomic weight, is very abundant in resources and thus is easy to supply and receive, and is inexpensive, non-toxic, and environmentally friendly.

[0006] In addition, lithium-sulfur batteries have a conversion reaction between lithium ions and sulfur (S 8 +16Li + +16e - →8Li 2 S) has a theoretical discharge capacity of 1675 mAh / g, and if lithium metal (theoretical capacity: 3860 mAh / g) is used as the negative electrode, the theoretical energy density is 2600 Wh / kg. Because the energy density of lithium-sulfur batteries is much higher than other battery systems currently being studied (Ni-MH battery: 450 Wh / kg; Li-FeS battery: 480 Wh / kg; Li-MnO 2 The theoretical energy density of lithium-sulfur battery is 1000Wh / kg; Na-S battery: 800Wh / kg) and lithium-ion battery (250Wh / kg), so lithium-sulfur battery is a battery that can meet the requirements of economic efficiency and environmental friendliness as well as high performance of the battery, and is currently being actively studied.

[0007] A positive electrode for a lithium-sulfur battery is generally manufactured by coating a positive electrode slurry including a positive electrode active material, a conductive material, a binder, and a solvent on a positive electrode collector, drying it, and then compression molding it.

[0008] However, in the case of lithium-sulfur batteries, the physical properties of the cathode slurry are particularly important factors in the preparation of the cathode slurry because it greatly affects the configuration of the cathode and the performance of the battery.

[0009] Therefore, various techniques have been proposed to improve the physical properties of cathode slurries in Li-S batteries.

[0010] For example, Korean Patent Publication No. 2019-0085874 discloses that by incorporating a lower alcohol having 1 to 5 carbon atoms into the positive electrode slurry, the dispersibility of the positive electrode slurry can be improved.

[0011] In addition, Korean Patent Publication No. 2017-0081840 discloses that the dispersibility and coating performance of the positive electrode slurry can be improved by preparing a pre-dispersed solution containing a conductive material and a solvent and mixing the pre-dispersed solution with an active material and a binder to prepare a positive electrode slurry.

[0012] The inventions disclosed in these patents improve the dispersibility, rheological properties, etc. of the positive electrode slurry to a certain extent by changing the composition or preparation method of the positive electrode slurry, but the effect is not sufficient. In particular, when additives are introduced to improve the physical properties of the positive electrode slurry, there is a problem of performance degradation of the lithium-sulfur battery. Therefore, it is necessary to further develop a positive electrode slurry for lithium-sulfur batteries that has excellent dispersibility and fluidity even with a high solid content.

[0013] Prior art literature

[0014] Patent Literature

[0015] Korean Patent Publication No. 2019-0085874 (July 19, 2019), Slurry composition for forming cathode, cathode manufactured thereby, and battery comprising the same

[0016] Korean Patent Publication No. 2017-0081840 (July 13, 2017), Preparation method of positive electrode slurry for lithium secondary battery Summary of the invention

[0017] Technical issues

[0018] Therefore, as a result of various studies conducted to solve the above-mentioned problems, the inventors of the present invention have found that when the ratio of the average particle size of the positive electrode active material to the positive electrode slurry and the phase angle of the positive electrode slurry are adjusted, the overall physical properties of the positive electrode slurry for lithium-sulfur batteries can be improved without changing the composition or preparation method of the positive electrode slurry, thereby completing the present invention.

[0019] Therefore, an object of the present invention is to provide a positive electrode slurry for a lithium-sulfur battery, which has improved fluidity and processability even while having a high solid content.

[0020] In addition, another object of the present invention is to provide a positive electrode for a lithium-sulfur battery prepared from the positive electrode slurry for a lithium-sulfur battery and a lithium-sulfur battery comprising the positive electrode for a lithium-sulfur battery.

[0021] Technical Solution

[0022] In order to achieve the above object, the present invention provides a positive electrode slurry for a lithium-sulfur battery, wherein the positive electrode slurry comprises: a positive electrode active material, a conductive material, a binder and a solvent, wherein the average particle size (D 50 ) and the average particle size (D 50 ) is less than 1.5, and the phase angle of the positive electrode slurry at 1 Hz is greater than 50°.

[0023] In addition, the present invention provides a positive electrode for a lithium-sulfur battery, which includes a positive electrode active material layer formed using the positive electrode slurry for a lithium-sulfur battery.

[0024] In addition, the present invention provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the positive electrode for the lithium-sulfur battery.

[0025] Beneficial Effects

[0026] The positive electrode slurry for lithium-sulfur batteries of the present invention exhibits excellent fluidity even when the solid content is high, thereby making it possible to manufacture a positive electrode for lithium-sulfur batteries having excellent electrochemical properties and improve the productivity and economic feasibility of the manufacturing process of the positive electrode for lithium-sulfur batteries. DETAILED DESCRIPTION

[0027] Hereinafter, the present invention will be described in more detail.

[0028] The terms and words used in this specification and claims should not be construed as limited to common or dictionary terms, and should be construed as meanings and concepts consistent with the technical idea of ​​the present invention on the basis of the principle that the inventor can appropriately define the concepts of the terms to describe his invention in the best possible manner.

[0029] The terms used herein are only used for the purpose of describing specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, the singular expressions "a", "a", "the" and "said" include plural indicators. It should be understood that the terms used in this specification such as "comprising" or "having" are intended to clearly indicate the presence of the described features, numbers, steps, operations, components, parts or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, numbers, steps, operations, components, parts or combinations thereof.

[0030] As used herein, the term "average particle size (D 50 )" refers to the corresponding particle diameter when the cumulative volume percentage reaches 50% in the particle size distribution curve of the particles, and can be measured using a laser diffraction method, for example.

[0031] The term "composite material" as used herein refers to a material in which two or more materials are combined to exhibit more effective functions while forming phases that are physically and chemically different from each other.

[0032] Lithium-sulfur batteries have higher theoretical discharge capacity and theoretical energy density than other secondary batteries, and are attracting attention as next-generation secondary batteries because sulfur, which is used as a main material of the positive electrode active material, has the advantages of being abundant, low-cost, and environmentally friendly.

[0033] The performance of such lithium-sulfur batteries may vary depending on the characteristics of the various components that constitute the battery. Among them, the composition of the electrode directly affects the performance of the battery. In particular, the solid concentration of the slurry constituting the positive electrode and the loading amount of the active material have a significant impact on the processability in the positive electrode manufacturing and the performance of the positive electrode formed thereby.

[0034] Generally, in the case of positive electrode slurries for lithium-sulfur batteries, there are problems in that the dispersibility of solids is low, whereby the surface state of the positive electrode deteriorates, such as cracks or particle aggregation occurring on the surface of the positive electrode, and these phenomena are further accelerated as the amount of positive electrode active material loading increases.

[0035] In order to solve these problems, in the prior art, a method of preparing a positive electrode slurry by adding an additive to the positive electrode slurry, separately dispersing some components contained in the positive electrode slurry and then mixing them, or injecting an excess solvent has been proposed. However, in this case, there are limitations such as additives such as polymer dispersants acting as resistors in the battery and adversely affecting battery performance, and the solid concentration of the positive electrode slurry is reduced and thus it is difficult to load the active material into the positive electrode at a high loading amount, and there is a disadvantage of low manufacturing process efficiency.

[0036] Therefore, the present invention provides a positive electrode slurry for a lithium-sulfur battery, which has a high solid content and excellent fluidity even without additional additives or changes in the manufacturing process by adjusting the average particle size ratio between the positive electrode active material and the positive electrode slurry to maintain the phase angle of the positive electrode slurry within a specific range.

[0037] Specifically, the positive electrode slurry according to the present invention is used to manufacture a positive electrode for a lithium-sulfur battery, wherein the positive electrode slurry comprises a positive electrode active material, a conductive material, a binder and a solvent, and the average particle size (D 50 ) and the average particle size (D 50 ) is less than 1.5, and the phase angle (δ) measured under the condition that the frequency of the positive electrode slurry is 1 Hz is greater than 50°.

[0038] In the present invention, the average particle size of the positive electrode slurry refers to the particle size of the positive electrode slurry itself finally obtained by mixing the positive electrode active material, the conductive material and the binder in a solvent. Generally, the average particle size of the positive electrode slurry may depend on the average particle size of the positive electrode active material contained therein. However, because the particle size of the positive electrode active material varies due to the mixing process used for dispersion during the preparation of the positive electrode slurry, the average particle size of the positive electrode slurry and the average particle size of the positive electrode active material are different from each other.

[0039] According to the present invention, by adjusting the ratio of the average particle size of the positive electrode active material to the positive electrode slurry to below a specific range, the active surface of the positive electrode active material is relatively small, thereby improving the dispersibility of the positive electrode active material, the conductive material and the binder, and the positive electrode active material is weakly combined with the binder to increase the fluidity corresponding to the viscosity while reducing the elasticity of the positive electrode slurry, thereby increasing the final solid content in the positive electrode slurry compared to the prior art. In addition, by reducing the viscosity of the positive electrode slurry, the fluidity can be improved and thus the processability can be improved.

[0040] The average particle size of the positive electrode active material (D 50 ) can be 28 μm to 60 μm, preferably 30 μm to 55 μm, more preferably 30 μm to 50 μm.

[0041] The average particle size of the positive electrode slurry containing the positive electrode active material, the conductive material and the binder (D 50 ) can be 20 μm to 40 μm, preferably 25 μm to 40 μm, and more preferably 25 μm to 35 μm.

[0042] The average particle size of the positive electrode active material (D 50 ) and the average particle size of the positive electrode slurry (D 50) can be 1.5 or less, preferably 0.1 to 1.5, more preferably 0.2 to 1.5, still more preferably 0.5 to 1.5, and most preferably 1.0 to 1.5. In the present invention, the ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode slurry corresponds to "average particle size of the positive electrode active material / average particle size of the positive electrode slurry". When the ratio of the average particle size of the positive electrode active material to the average particle size of the positive electrode slurry is within the above range, the various components contained in the positive electrode slurry can be uniformly dispersed, and they are in a state of aggregation to a certain extent, and the positive electrode slurry can have a liquid-like flow behavior.

[0043] The positive electrode slurry according to the present invention has the positive electrode active material and the average particle size (D 50 ) ratio and the phase angle at 1 Hz can be 50° or more, preferably 50° to 70°. In the present invention, the phase angle is measured at a frequency of 1 Hz using a rheometer by a method known in the art. If the phase angle of the positive electrode slurry exceeds 70°, there is a problem that the slurry may flow off the substrate during coating.

[0044] In addition, at 23 °C and a shear rate of 0.25 s -1 The viscosity of the positive electrode slurry of the present invention is 30 to 80 Pa·s, preferably 32 to 70 Pa·s, more preferably 35 to 60 Pa·s, still more preferably 40 to 60 Pa·s, and most preferably 43 to 58 Pa·s when measured under the conditions of . If the viscosity of the positive electrode slurry is less than the above range, the coating performance may decrease. On the contrary, if the viscosity of the positive electrode slurry exceeds the above range, the elasticity may increase and the solid content may also decrease.

[0045] When the ratio of the positive electrode active material to the average particle size of the positive electrode slurry is adjusted to a specific range without changing the composition or preparation process of the positive electrode slurry, the positive electrode slurry according to the present invention can meet the phase angle condition, thereby greatly improving the cohesion and fluidity while having a high solid content.

[0046] Hereinafter, various components contained in the positive electrode slurry according to the present invention will be described.

[0047] The positive electrode slurry according to the present invention is used for a lithium-sulfur battery and contains a sulfur-carbon composite material as a positive electrode active material.

[0048] The sulfur-carbon composite material includes a porous carbon material and sulfur contained in at least a portion of the inner surface and the outer surface of the porous carbon material. Sulfur used as a positive electrode active material in a lithium-sulfur battery is used in combination with a conductive material such as a carbon material because it alone does not have conductivity. Therefore, sulfur is contained in the form of a sulfur-carbon composite material.

[0049] Sulfur may include at least one selected from the following: elemental sulfur (S8 ) and sulfur compounds. The positive electrode active material may include at least one selected from the following: inorganic sulfur, Li 2 S n (n≥1), disulfide compounds, organic sulfur compounds and carbon-sulfur polymers ((C 2 S x ) n , x=2.5 to 50, n≥2). Preferably, the positive electrode active material may be inorganic sulfur.

[0050] The sulfur-carbon composite material contains a porous carbon material, which not only provides a framework that can uniformly and stably fix sulfur, but also makes up for the low electrical conductivity of sulfur, allowing the electrochemical reaction to proceed smoothly.

[0051] The porous carbon material can be generally manufactured by carbonizing the precursors of various carbon materials. The porous carbon material may contain non-uniform pores therein, the average diameter of the pores being in the range of 1 to 200 nm, and the porosity may be in the range of 10% to 90% of the total volume of the porous carbon material. If the average diameter of the pores is smaller than the above range, the pore size is only at the molecular level and thus the impregnation of sulfur is impossible. On the contrary, if the average diameter of the pores exceeds the above range, the mechanical strength of the porous carbon material is weakened, which is not preferred for the manufacturing process applied to the electrode.

[0052] The shape of the porous carbon material is in the form of spheres, rods, needles, plates, tubes, or blocks, and can be used without limitation as long as it is generally used in lithium-sulfur batteries.

[0053] The porous carbon material may have a porous structure or a high specific surface area, and may be any one of the porous carbon materials conventionally used in the art. For example, the porous carbon material may be, but is not limited to, at least one selected from the following: graphite; graphene; carbon black such as Deco black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); graphites such as natural graphite, artificial graphite, and expanded graphite; and activated carbon. Preferably, the porous carbon material may be a carbon nanotube.

[0054] The sulfur in the sulfur-carbon composite material is located on at least one of the inner and outer surfaces of the above-mentioned porous carbon material, for example, it may be present in an area of ​​less than 100%, preferably 1 to 95%, and more preferably 40 to 96% of the entire inner and outer surfaces of the porous carbon material. If the sulfur as described above is present on the inner and outer surfaces of the porous carbon material within the above range, it can show a maximized effect in terms of electron migration area and wettability with the electrolyte. Specifically, because the sulfur is thinly and uniformly impregnated on the inner and outer surfaces of the porous carbon material within the above range, the electron migration contact area can be increased during the charge / discharge process. If the sulfur is located in 100% of the area of ​​the entire inner and outer surfaces of the porous carbon material, the porous carbon material is completely covered with sulfur, so that it cannot receive electrons because it has poor wettability and poor contact with the electrolyte, so it cannot participate in the electrochemical reaction.

[0055] Relative to 100% by weight of the sulfur-carbon composite material, the sulfur content in the sulfur-carbon composite material can be 65 to 90% by weight, preferably 70 to 85% by weight, and more preferably 72 to 80% by weight. If the sulfur content is lower than the above range, as the content of the porous carbon material in the sulfur-carbon composite material increases relatively, the specific surface area increases, and thus when the positive electrode is manufactured, the content of the binder increases. The increase in the amount of binder will eventually increase the sheet resistance of the positive electrode and thus act as an insulator to prevent electrons from passing through, thereby deteriorating the performance of the battery. On the contrary, if the sulfur content exceeds the above range, the sulfur that is not combined with the porous carbon material gathers between them or dissolves again to the surface of the porous carbon material, thereby becoming difficult to receive electrons and cannot participate in the electrochemical reaction, resulting in a loss of battery capacity.

[0056] The present invention has no particular limitation on the method for preparing the sulfur-carbon composite material, and a method commonly used in the art can be used. For example, a method can be used in which sulfur and porous carbon materials are simply mixed and then heat-treated to thereby composite them.

[0057] In addition to the above components, the positive electrode active material may further include at least one selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0058] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., and the IIIA group elements may include Al, Ga, In, Tl, etc., and the IVA group elements may include Ge, Sn, Pb, etc.

[0059] The positive electrode slurry for lithium-sulfur batteries according to the present invention may contain a conductive material to impart conductivity. The conductive material is a material that electrically connects the electrolyte and the positive electrode active material to serve as a path for electrons to move from the current collector to the positive electrode active material, and the conductive material can be used without limitation as long as it has conductivity.

[0060] For example, as the conductive material, the following substances can be used alone or in combination: carbon black such as Super-P, Deko black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; carbon derivatives such as carbon nanotubes, graphene and fullerene; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene and polypyrrole.

[0061] The positive electrode slurry for lithium-sulfur battery according to the present invention may contain a binder to provide adhesion to the positive electrode collector. The binder holds the positive electrode active material in the positive electrode collector and organically connects the positive electrode active material to further increase the binding force between them, and as the binder, any binder known in the art can be used.

[0062] For example, the adhesive can be the following substances or a mixture or copolymer of two or more thereof: fluororesin adhesives, including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); rubber adhesives, including styrene-butadiene rubber (SBR), nitrile rubber and styrene-isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; polyol adhesives; polyolefin adhesives, including polyethylene and polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0063] The positive electrode slurry for a lithium-sulfur battery according to the present invention may contain a solvent. The solvent may be a solvent that can uniformly disperse the positive electrode active material, the conductive material, and the binder and can be easily dried.

[0064] For example, the solvent is an aqueous solvent and most preferably water, in which case water can be distilled water or deionized water. However, the present invention is not necessarily limited thereto and, if desired, can be used together with an organic solvent such as a lower alcohol that is easy to be miscible with water as a solvent. The lower alcohol can include methanol, ethanol, propanol, isopropanol and butanols, and preferably, they can be used in a mixture with water.

[0065] There is no particular limitation on the method for preparing the positive electrode slurry for a lithium-sulfur battery according to the present invention, and a method known to those skilled in the art or various methods modified therefrom can be used.

[0066] For example, the positive electrode slurry for the lithium-sulfur battery can be prepared by mixing a conductive material, a binder, and a solvent to prepare a mixture, and then adding the positive electrode active material to the mixture and stirring. At this time, it is desirable to adjust the average particle size of the positive electrode active material to be injected and the average particle size of the positive electrode slurry finally prepared so that the average particle size (D 50 ) ratio satisfies the condition of being less than 1.5 as described above.

[0067] In particular, in the case of the method for preparing a positive electrode slurry for a lithium-sulfur battery according to the present invention, when a positive electrode active material having an adjusted average particle size is used as a raw material, the process energy can be minimized until the average particle size of the positive electrode slurry finally prepared is reached, thereby having beneficial advantages in terms of economic feasibility and process efficiency. Specifically, in the case of a conventional method, a process energy of 60W or more is required to prepare a positive electrode slurry. However, in the case of the present invention, even if the process energy is 50W or less, the average particle size of the positive electrode slurry can be fully achieved, which is preferred.

[0068] Conventional dispersing devices can be used for mixing or stirring. For example, a paste mixer, a vibrator, a homogenizer, a paint vibrator, an ultrasonic homogenizer, a bead mill, a roller mill, an apex mill, a vibrating ball mill, and a dispersing device using a mixture thereof can be used. Preferably, a bead mill or a vibrating ball mill can be used, and when a bead mill is used, zirconia beads can be used as a dispersion medium.

[0069] Because the average particle size (D 50 ) is less than 1.5, and the phase angle of the positive electrode slurry at 1 Hz satisfies more than 50°, so it has good cohesion and fluidity under conditions of high solid content, thereby greatly improving the electrochemical properties and manufacturing processability of the positive electrode.

[0070] In addition, the present invention provides a positive electrode for a lithium-sulfur battery, comprising the positive electrode slurry for a lithium-sulfur battery.

[0071] The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector. In this case, the positive electrode active material layer includes the positive electrode slurry for lithium-sulfur battery of the present invention.

[0072] The positive electrode current collector supports the positive electrode active material and is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. As the positive electrode current collector, for example: copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; copper or stainless steel surface-treated with carbon, nickel, silver, etc.; aluminum-cadmium alloy, etc. can be used.

[0073] The positive electrode current collector can enhance the bonding force with the positive electrode active material by having fine concavoconvexities on its surface, and may be formed into various forms such as a film, a sheet, a foil, a screen, a net, a porous body, a foamed body, or a nonwoven fabric.

[0074] The positive electrode active material layer is formed using the positive electrode slurry for a lithium-sulfur battery according to the present invention, which may include a positive electrode active material, a conductive material, and a binder.

[0075] Specific details of the positive electrode active material, the conductive material and the binder are as described above.

[0076] There is no particular limitation on the method of manufacturing the positive electrode, and a method known to those skilled in the art or various methods modified therefrom may be used.

[0077] For example, the positive electrode may be manufactured by coating the positive electrode slurry for a lithium-sulfur battery of the present invention on at least one surface of a positive electrode collector and thereby forming a positive electrode active material layer.

[0078] The present invention is not particularly limited to the coating method, and there can be mentioned, for example, methods such as a doctor blade method, a die casting method, a comma coating method, and a screen printing method. In addition, after forming on a separate substrate, the positive electrode slurry can be coated on the positive electrode collector by pressing or laminating.

[0079] After coating, a drying process for removing the solvent may be performed. The drying process is performed at a temperature and time at a level that can fully remove the solvent, and the conditions may vary depending on the type of solvent, and thus are not particularly limited in the present invention. For example, there may be mentioned: a drying method by warm air, hot air or low-humidity air; a vacuum drying method; and a drying method by irradiating (far) infrared rays or electron beams. The drying speed is adjusted in a manner to remove the solvent as quickly as possible within a speed range that does not cause the positive electrode active material layer to rupture due to normal stress concentration or within a speed range that does not cause the positive electrode active material layer to peel off from the positive electrode collector.

[0080] In addition, after drying, the density of the positive electrode active material layer in the positive electrode can be increased by pressing the current collector. As a pressing method, methods such as molding and calendaring can be mentioned.

[0081] In addition, the present invention provides a lithium-sulfur battery, wherein the lithium-sulfur battery comprises the positive electrode for the lithium-sulfur battery.

[0082] The lithium-sulfur battery comprises: a positive electrode; a negative electrode; and an electrolyte disposed therebetween, wherein the positive electrode comprises the positive electrode for a lithium-sulfur battery according to the present invention.

[0083] The positive electrode is as described above.

[0084] The negative electrode may include a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate.

[0085] The negative electrode current collector is used to support the negative electrode active material layer and is as described in the positive electrode.

[0086] In addition to the negative electrode active material, the negative electrode active material layer may further include a conductive material, a binder, etc. At this time, the binder is as described above.

[0087] The conductive material is a material that acts as a path for electrons to migrate from the current collector to the negative electrode active material by electrically connecting the electrolyte and the negative electrode active material. The conductive material can be used without limitation as long as it has conductivity.

[0088] For example, as the conductive material, the following substances can be used alone or in combination: graphite such as natural graphite or artificial graphite; carbon black such as Super-P, Deko black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; carbon derivatives such as carbon nanotubes and fullerenes; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene and polypyrrole.

[0089] The negative electrode active material may include: + ) material; a material capable of reacting with lithium ions to reversibly form a lithium-containing compound; lithium metal; or a lithium alloy.

[0090] Able to reversibly insert or deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0091] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of a lithium metal film or lithium metal powder.

[0092] There is no particular limitation on the method for forming the negative electrode active material, and a method for forming a layer or film commonly used in the art can be used. For example, methods such as compression, coating and deposition can be used. In addition, the negative electrode of the present invention also includes the case where a metallic lithium film is formed on a metal plate by initial charging after assembling the battery without a lithium film on the current collector.

[0093] The electrolyte contains lithium ions and is intended to cause electrochemical oxidation or reduction reactions in the positive electrode and the negative electrode by them.

[0094] The electrolyte may be a non-aqueous electrolyte solution or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte, and contains an electrolyte salt and an organic solvent.

[0095] The electrolyte salt contained in the nonaqueous electrolyte is a lithium salt. The lithium salt can be used without limitation as long as it is a lithium salt commonly used in an electrolyte for a lithium secondary battery. For example, the lithium salt may be LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 ,LiC 4 BO 8 、LiAsF 6 、LiSbF 6 、LiAlCl 4 , CH 3 SO 3 Li, CF 3 SO 3 Li, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 ) 2 NLi, (SO 2 F) 2 NLi, (CF 3 SO 2 ) 3 CLi, lithium chloroborane, lithium lower aliphatic carboxylate, tetraphenylborate, lithium imide, etc.

[0096] The concentration of the lithium salt can be determined in consideration of ion conductivity, solubility, etc., and can be, for example, 0.1 to 4.0 M, preferably 0.5 to 2.0 M. If the concentration of the lithium salt is less than the above range, it is difficult to ensure ion conductivity suitable for battery operation. On the other hand, if the concentration exceeds the above range, the viscosity of the electrolyte increases to reduce the mobility of lithium ions, and the decomposition reaction of the lithium salt itself may increase to deteriorate the performance of the battery. Therefore, the concentration is appropriately adjusted within the above range.

[0097] As the organic solvent contained in the nonaqueous electrolyte, organic solvents generally used in electrolytes for lithium secondary batteries can be used without limitation, and for example, ethers, esters, amides, linear carbonates, cyclic carbonates and the like can be used alone or in combination of two or more thereof.

[0098] The ether compounds may include acyclic ethers and cyclic ethers.

[0099] For example, the acyclic ether may be, but is not limited to, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0100] For example, the cyclic ether may be, but is not limited to, at least one selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxolane, 1,4-dioxolane, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran ... alkanes, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene and dimethyl isosorbide.

[0101] Examples of the ester of the organic solvent may be, but are not limited to, any one selected from the following or a mixture of two or more thereof: methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone.

[0102] Specific examples of the linear carbonate compound may be representatively, but not limited to, any one selected from the following or a mixture of two or more thereof: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methylpropyl carbonate and ethylpropyl carbonate.

[0103] In addition, specific examples of cyclic carbonate compounds can be any one selected from the following or a mixture of two or more thereof: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate and halides thereof. Examples of these halides include, but are not limited to, fluoroethylene carbonate (FEC) and the like.

[0104] In addition to the above-mentioned electrolyte salt and organic solvent, the electrolyte may further contain a nitric acid or nitrous acid compound as an additive, which has the function of forming a stable film on the lithium metal electrode as the negative electrode and improving the charge / discharge efficiency.

[0105] The present invention has no particular limitation on the nitric acid or nitrous acid compound, but it can be at least one selected from the following: inorganic nitric acid or nitrous acid compound such as lithium nitrate (LiNO 3 ), potassium nitrate (KNO 3 ), cesium nitrate (CsNO 3 ), barium nitrate (Ba(NO 3 ) 2 ), ammonium nitrate (NH 4 NO 3 ), lithium nitrite (LiNO 2 ), potassium nitrite (KNO 2 ), cesium nitrite (CsNO 2 ) and ammonium nitrite (NH 4 NO 2 ); organic nitric acid or nitrous acid compounds such as methyl nitrate, dialkyl imidazole nitrate , guanidine nitrate, imidazole nitrate , pyridine nitrate , ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite and octyl nitrite; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, preferably lithium nitrate.

[0106] The electrolyte may be injected into the electrochemical device at an appropriate stage during the electrochemical device manufacturing process according to the manufacturing process and the required performance of the final product. That is, the injection may be performed before assembling the electrochemical device or at the final stage of assembling the electrochemical device.

[0107] A separator may be further included between the positive electrode and the negative electrode.

[0108] The separator may be made of a porous non-conductive or insulating material that separates or insulates the positive electrode and the negative electrode from each other and enables lithium ions to be transported between the positive electrode and the negative electrode. The separator may be used without particular limitation as long as it is used as a separator in a conventional lithium secondary battery. The separator may be an independent component such as a film, or may be a coating added to the positive electrode and / or the negative electrode.

[0109] It is preferred that the separator has excellent wettability to the electrolyte and low resistance to ion migration of the electrolyte.

[0110] The separator can be made of a porous substrate, and the porous substrate can be used as long as it is a porous substrate commonly used for secondary batteries, and a porous polymer film can be used alone or by laminating them. For example, a non-woven fabric or a polyolefin porous film made of glass fiber with a high melting point, polyethylene terephthalate fiber, etc. can be used, but it is not limited to this.

[0111] The present invention has no particular restrictions on the material of the porous substrate, and any material can be used as long as it is a porous substrate commonly used in electrochemical devices. For example, the porous substrate may include at least one material selected from the following: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobis[epoxy]ene), ... azoles) and polyarylates.

[0112] The thickness of the porous substrate is not particularly limited, but may be 1 μm to 100 μm, preferably 5 μm to 50 μm. Although the thickness range of the porous substrate is not particularly limited to the above range, if the thickness is much thinner than the above lower limit, the mechanical properties are deteriorated, and thus the separator may be easily damaged during battery use.

[0113] The average diameter and porosity of pores present in the porous substrate are also not particularly limited, but may be 0.001 μm to 50 μm and 10% to 95%, respectively.

[0114] The lithium secondary battery according to the present invention can be manufactured through lamination, stacking, and folding processes of the separator and the electrodes in addition to a general winding process.

[0115] The shape of the lithium secondary battery is not particularly limited, and may be various shapes such as a cylindrical shape, a laminate shape, and a coin shape.

[0116] Furthermore, the present invention provides a battery module including the above-mentioned lithium secondary battery as a unit cell.

[0117] The battery module can be used as a power source for medium or large-sized devices requiring high temperature stability, long cycle characteristics, high capacity characteristics, and the like.

[0118] Examples of these medium to large devices may include, but are not limited to: power tools powered and moved by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; power storage systems, etc.

[0119] Preferred Implementation

[0120] Hereinafter, in order to help understand the present invention, preferred embodiments of the present invention will be described. However, it will be apparent to those skilled in the art that the following examples are only used to illustrate the present invention, and that various changes and variants can be accomplished within the scope and spirit of the present invention, and such changes and variants are within the scope of the appended claims.

[0121] Examples and Comparative Examples

[0122] Example 1

[0123] 5 wt % of vapor grown carbon fiber (VGCF) as a conductive material and 4 wt % of styrene butadiene rubber / carboxymethyl cellulose (SBR / CMC) as a binder were added to a stainless steel slurry container with a capacity of 500 ml, as well as water and zirconia beads, and mixed in a bead mill.

[0124] Thereafter, 91 wt % of a sulfur-carbon composite material (S:CNT=70:30 (weight ratio)) having an average particle size (D50) of 45.9 μm was added to the mixture and stirred at 48 W to prepare a 50 ) is 29.9 μm. At this time, the solid content of the prepared positive electrode slurry for lithium-sulfur battery is 31%.

[0125] Example 2

[0126] Except for using the same amount of average particle size (D 50 ) of 34.2 μm as the positive electrode active material, and stirred at 48 W to prepare 50 ) was 29.5 μm, a positive electrode slurry for a lithium-sulfur battery was prepared in the same manner as in Example 1. At this time, the solid content of the prepared positive electrode slurry for a lithium-sulfur battery was 31%.

[0127] Comparative Example 1

[0128] Except for using the same amount of average particle size (D 50 ) of 51.3 μm as the positive electrode active material, and stirred at 60 W to prepare 50 ) was 29.5 μm, a positive electrode slurry for a lithium-sulfur battery was prepared in the same manner as in Example 1. At this time, the solid content of the prepared positive electrode slurry for a lithium-sulfur battery was 31%.

[0129] Experimental Example 1. Evaluation of physical properties of positive electrode slurry

[0130] (1) Viscosity

[0131] The viscosity of the positive electrode slurry in the examples and comparative examples was measured. Specifically, the viscosity was measured using a rheometer (Discovery HR-1, TA Instruments Korea) at 23° C. and 1 rpm. The results obtained at this time are shown in Table 1 below.

[0132] (2) Phase angle

[0133] The phase angles of the positive electrode slurries in the examples and comparative examples were measured. Specifically, a rheometer (Discovery HR-1, TA Instruments Korea) was used to apply a stress of 0.08% at 23°C and perform a frequency sweep at a frequency of 1 Hz to measure the phase angles. The results obtained at this time are shown in Table 1 below.

[0134] Table 1:

[0135]

[0136] As can be seen from Table 1, in the case of the positive electrode slurry according to the example, the overall physical properties of the slurry are more excellent than those of the comparative example.

[0137] It is generally believed that as the phase angle of the fluid increases, the cohesion and fluidity of the fluid are improved. Referring to Table 1, it can be seen that in the case of the positive electrode slurries according to Examples 1 and 2, the phase value is greater than that of the positive electrode slurry according to Comparative Example 1, so the cohesion and fluidity are excellent.

[0138] In addition, it can be seen that the positive electrode slurries of Examples 1 and 2 have lower viscosities than Comparative Example 1, and thus they can exhibit excellent coating properties on the surface of the positive electrode collector.

[0139] Furthermore, it can be confirmed from Example 2 and Comparative Example 1 that, although positive electrode slurries having the same average particle size were prepared, the viscosity and phase angle of the finally prepared positive electrode slurry differed depending on the average particle size of the input positive electrode active material.

[0140] From these results, it can be confirmed that in the case of the positive electrode slurry according to the present invention, since the average particle size (D 50 ) is less than 1.5, so the cohesion, fluidity and coating performance can be improved while the solid content is high.

Claims

1. A positive electrode slurry for a lithium-sulfur battery, the positive electrode slurry comprising: a positive electrode active material, a conductive material, a binder and a solvent, The average particle size of the positive electrode active material is D 50 The average particle size D of the positive electrode slurry 50 The ratio is 1.2 to 1.

5. The positive electrode slurry has a phase angle of 50° to 70° measured at 1 Hz by applying a stress of 0.08% at 23°C using a rheometer, The positive electrode active material comprises a sulfur-carbon composite material.

2. The positive electrode slurry for lithium-sulfur battery according to claim 1, wherein the positive electrode active material has an average particle size D of 28 μm to 60 μm. 50 .

3. The positive electrode slurry for lithium-sulfur battery according to claim 1, wherein the positive electrode slurry has an average particle size D of 20 μm to 40 μm. 50 .

4. The positive electrode slurry for lithium-sulfur battery according to claim 1, wherein the positive electrode slurry is heated at 23°C, 1 rpm and 0.25 s -1 The viscosity measured under the condition of shear rate is 30Pa·s to 80Pa·s. 5 . The positive electrode slurry for a lithium-sulfur battery according to claim 1 , wherein the sulfur-carbon composite material comprises a porous carbon material and sulfur present in at least a portion of an inner surface and an outer surface of the porous carbon material. 6 . The positive electrode slurry for a lithium-sulfur battery according to claim 5 , wherein the porous carbon material comprises at least one selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon fibers and activated carbon.

7. The positive electrode slurry for lithium-sulfur battery according to claim 5, wherein the sulfur comprises at least one selected from the following: inorganic sulfur; Li2S n wherein n≥1; and organic sulfur compounds. 8 . A positive electrode for a lithium-sulfur battery, comprising a positive electrode active material layer formed using the positive electrode slurry for a lithium-sulfur battery according to claim 1 .

9. A lithium-sulfur battery, comprising: the positive electrode for the lithium-sulfur battery according to claim 8; a negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Toothpaste

    KR1020200121526A

  • Apparatus for inhibiting formation of calcium based crystal and Apparatus for water treatment using the same

    KR1020210120228A

  • Method for preparing electrode active material slurry, and electrode active material slurry prepared by method

    CN105283987A

  • Method for predicting processability of electrode slurry and selecting electrode binder

    CN110679014A

  • KR20190068066A